Monastic Experiences in Fostering Mental Wellbeing and Psychotherapeutic Practices in Ethiopia: A Case Study in Selected Monasteries - Tewachew, Abebe; Esmael, Zerihun (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
It is agreed among mental health experts that Religiosity or issues relating to the human spirit has a role in fostering overall health. This study aimed to investigate the monastic experiences in fostering mental wellbeing and thoroughly explore the Monastic experiences in the Ethiopian Orthodox Tewahedo Church. A case study design was employed to achieve the objectives of the study. Purposive samples of nine monks/nuns were interviewed to generate conclusions. The generated findings suggest Monks/nuns in the Ethiopian Orthodox Tewahedo Church (EOTC) monasteries devote their time to undistracted prayer, meditation, obedience and fasting, which in turn supports and/or correlates with mental wellness and positive psychological conceptions. Mindfulness in the monasteries appears to be the solution, which is usually being practiced in the Ethiopian Orthodox Tewahedo Church Monasteries. Mindfulness-oriented therapy in Psychology is getting attention towards its role regarding holistic aspect of health. It is recommended that an updating of training programs for psychotherapists, including the monastic experiences either in formal instructional curriculum or short-term training programs that play its part in achieving the new paradigm in mental health sector. This research hoped to create an insight and courage to look for the faith-based healing practices in order to develop enabling policy framework to promote mental health.